Conformational Landscapes and Energetics of Carbon Nanohoops and their Ring-in-Ring Complexes - Geue, Niklas; Freiberger, Markus; Frühwald, Stefan; Görling, Andreas; Drewello, Thomas; Barran, Perdita E. (Journal of Physical Chemistry Letters, 2024)
Carbon nanohoops are promising precursors for the synthesis of nanotubes, whose structural dynamics are not well understood. Here, we investigate the conformational landscape and energetics of cycloparaphenylenes (CPPs), a methylene-bridged CPP and a carbon nanobelt. These nanohoops can form host-guest complexes with other rings, and understanding their structure is crucial for predicting their properties and identifying potential applications. We used a combination of ion mobility, tandem mass spectrometry, and density functional theory to characterize the nanohoops and their ring-in-ring complexes, following the energetics and conformations of their disassembly from intact complexes to fragment ions. Our results show structural integrity of the nanohoops and host-guest complexes. They also reveal interesting trends in size, packing density, stability, and structure between [6]CPP, the methylene-bridged CPP, and the carbon nanobelt as guests in ring-in-ring complexes. Taken together, our work illustrates how mass spectrometry data can help to unravel the rules that govern the formation of carbon nanohoop assemblies.
CRIS-Team Scopus Importer:2024-07-05